2022
DOI: 10.3389/fpsyg.2022.838878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leisure Activities on the Cognitive Ability of Older Adults: A Latent Variable Growth Model Analysis

Abstract: Based on the data of four periods of CLHLS (2008, 2011, 2014, 2018), the latent variable growth model (LGCM) was applied to 2344 older adults who completed four follow-up surveys, to study the trajectory of leisure activities and cognitive ability and explore the relationship between leisure activities and cognitive ability of older adults. The results showed that: (1) leisure activities and cognitive ability of older adults showed a non-linear downward trend; (2) leisure activities significantly and positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Another significant protective factor of CRCI is LA, which was reported among older adults in the community. 47 , 48 Few studies have examined the relationship between LAs and cognitive function in patients having cancer, and most studies have been conducted in community populations. Engaging in LAs in an enriched environment can increase brain-derived neurotrophic assessment and promote synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another significant protective factor of CRCI is LA, which was reported among older adults in the community. 47 , 48 Few studies have examined the relationship between LAs and cognitive function in patients having cancer, and most studies have been conducted in community populations. Engaging in LAs in an enriched environment can increase brain-derived neurotrophic assessment and promote synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to the life cycle theory, the decline in physical function accelerates over time as older people reach the end of their life cycle [ 51 ]. Furthermore, the cognition ability of older adults declined at an accelerated rate later in the life cycle [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown that activity participation levels in middle-aged and older adults increase or stabilize over time [ 11 , 12 ], in general, the academic community generally believes that it becomes increasingly difficult for middle-aged and older people to maintain active participation as they grow older [ 13 , 14 ]. The concept of life cycle is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…In psychology, it mainly refers to the life cycle of people and the life cycle of the family and also refers to the process of birth, growth, aging, illness, and death. Life cycle theory holds that after middle-aged people enter old age, their physiological and psychological processes experience a series of changes [ 14 ], which leads to changes in activity participation [ 6 ]. In a nutshell, the activity participation of the elderly (eg, leisure activities) gradually becomes simpler and decreases over time [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation